Breeding distribution and ecology of the black stork Ciconia nigra in the Sava alluvial wetlands, Croatia - Scneider-Jacoby, Martin (Acrocephalus, 1999)
During 1986-1988, a systematic ornithological study was carried out in the Sava wetlands in Croatia (Fig. l). The study area covers 1,766 km2 and supports a very high proportion of important biotopes; 612 km2 of floodplain, 522 km2 of autochthonous deciduous woodland (3/4 flooded), 119 km2 wet pastureland, 121 km2 hay meadows,16 km2 fish-ponds and 42 km2 of rivers (Tab. 1S. During the study, 469 observations of Black Storks were made and a total of 1,151 Black Storks seen. In 64% of the observations one stork was sighted, in 27% two individuals and on six occasions more than 30 birds were seen together (maximum 69): Most of the observations were conducted in April and May when the birds were making territorial flights over the riparian forests (Figs.2, 3). 81% of the sightings were made in the floodplain. 60% of the observations were made of birds either in or in flight over wooded areas, 16% in wet pastureland, 5% in meadowland, 4% on fish-ponds and 3% on the Sava's tributaries: Black storks were observed iri 44% of the 362 grid squares (2 x 2km, Figs. 4,6). Their distribution is diseussed. Nests were seen is 26 of thesquares, and in 45 grid squares territories existed. The population amountsto at least 70 breeding pairs. The area holds about 1 % of the Europeanpopulation and is therefore of international importance.
Keywords: bird; Birds; ptice; ornitologija; Ecology; črna štorklja; Population density; Hrvaška; Croatia; Animal nutrition; gnezdenje; ekologija; Behavior, animal